2015
DOI: 10.15277/bjdvd.2015.043
|View full text |Cite
|
Sign up to set email alerts
|

Necrobiosis lipoidica

Abstract: Necrobiosis lipoidica and granuloma annulare are granulomatous skin conditions that have been traditionally associated with diabetes mellitus, although recently the strength of association has been questioned. In the first section of this two-part article, we describe the suggested aetiology, clinical features, histology and treatment of necrobiosis lipoidica. It is found in 0.3% of patients with diabetes, but has also been reported with other systemic conditions. Clinically it appears as a waxy, atrophic, yel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
4
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(5 citation statements)
references
References 25 publications
(40 reference statements)
1
4
0
Order By: Relevance
“…7 It may be difficult to conduct a large study with a rare condition such as this. It has also been previously shown that many NLD patients have elevated HgbA1c at time of presentation, 13 as in this patient, which seems to suggest glucose control playing a role in NLD, but this finding may simply be a reactionary stress response over time to this skin condition. At this point, the relationship between the elevated HgbA1c at time of presentation and NLD remains elusive.…”
Section: Discussionsupporting
confidence: 65%
See 4 more Smart Citations
“…7 It may be difficult to conduct a large study with a rare condition such as this. It has also been previously shown that many NLD patients have elevated HgbA1c at time of presentation, 13 as in this patient, which seems to suggest glucose control playing a role in NLD, but this finding may simply be a reactionary stress response over time to this skin condition. At this point, the relationship between the elevated HgbA1c at time of presentation and NLD remains elusive.…”
Section: Discussionsupporting
confidence: 65%
“…These treatments can include several mentioned above and others like doxycycline, hydroxychloroquine, and colchicine. 13 In this case, the patient had already been using a suggested treatment for NLD. The patient was taking pentoxifylline when the lesions developed and the wounds worsened while she was taking the medication, leading to the conclusion, that for this patient, the medication did not have a benefit.…”
Section: Discussionmentioning
confidence: 97%
See 3 more Smart Citations